Переваги та недоліки різних методів досліджень фазово-структурних станів матеріалів (оглядова стаття) - Князєва (Постельник), Ганна Олександрівна; Князєв, Сергій Анатолійович; Ткачук, Микола Миколайович; Пінчук, Наталія Володимирівна (Національний технічний університет "Харківський політехнічний інститут", 2021)
У роботі наведений короткий огляд стандартних можливостей рентгенівських методик дослідження матеріалів з наведенням прикладів сучасного виконання елементного та рентгеноструктурного досліджень. Методи рентгенівських досліджень дають можливість виявити елементний та фазово-структурний стан. Завдяки сучасному програмному забезпеченню та електронним базам даних застосування донині складних методик стає простим і більш доступним. Практика взаємодії дослідників показує, що навіть спеціалістам у галузі рентгеноструктурного аналізу не завжди відомі сучасні методики обробки і розшифрування отриманих даних. Можливості та алгоритм дії при дослідженнях можуть бути цікавими для студентів, інженерів, дослідників матеріалознавчого та машинобудівного профілю.

The paper provides a brief overview of the standardcapabilities of X-ray techniques for studying materials with examples of modern performance of elemental and structural studies. X-ray research methods make it possible to reveal the elemental and phase-structural state. Thanks to modern software and electronic databases, the use of previously complex techniques is becoming simpler and more accessible. To illustrate the solution of specific problems, several examples of obtaining and decoding diffraction patterns and identifying the phase composition of the coating and ceramic material are given. An example of work in modern specialized software for acceleration and automation of phase identification is shown. For clarity, an example of identifying phases using electronic databasecards is presented, which is still used today for manual decoding. The practice of interaction between researchers shows that even specialists in the field of X-ray structural analysis are not always aware of modern methods of processing and decoding the obtained data. The possibilities and algorithm of action in research can be interesting forstudents, engineers, researchers of materials science and mechanical engineering profile.
Advantages and disadvantages of different methods for studying the phase-structural states of materials (a review)
Keywords: мікроскопія; рентгеноструктурний аналіз; рентгенофлуоресцентний аналіз; microscopy; X-raystructural analysis; X-rayfluorescence analysis